2022
DOI: 10.1177/09544089221095671
|View full text |Cite
|
Sign up to set email alerts
|

Parameter optimization and experimental validation of A-TIG welding of super austenitic stainless steel AISI 904L using response surface methodology

Abstract: Super austenitic stainless steel (SASS) is a premium stainless steel (SS) variant which finds applications in challenging environments. One of the premium grades of SS that falls under the said category is AISI 904L. Autogenous activated flux tungsten inert gas (A-TIG) welding is an established technique for fabricating sound steel joints which offers various advantages. In this context, this research aims to identify an optimum set of input process parameters to effectively employ A-TIG welding to fabricate 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Tungsten inert gas (TIG) welding was conducted using direct current single polarity (DCSP) from a power source characterised by drooping V-I static characteristics. A tungsten electrode of type A 203, typically sharpened to a cone angle of 60° with a flat tip ranging from 0.125 to 0.50mm, was employed [34]. The machine used for the TIG operation is a DC inverter TIG welder (model: PI 180 MT, manufacture: Powercon Electronics, Amperage range -10-180 A, welding rods -Phosphor bronze).…”
Section: Methodsmentioning
confidence: 99%
“…Tungsten inert gas (TIG) welding was conducted using direct current single polarity (DCSP) from a power source characterised by drooping V-I static characteristics. A tungsten electrode of type A 203, typically sharpened to a cone angle of 60° with a flat tip ranging from 0.125 to 0.50mm, was employed [34]. The machine used for the TIG operation is a DC inverter TIG welder (model: PI 180 MT, manufacture: Powercon Electronics, Amperage range -10-180 A, welding rods -Phosphor bronze).…”
Section: Methodsmentioning
confidence: 99%
“…The little serious circular segment given by the sharp anode is great for excellent and accurate welding. Since the cathode will not be consumed during welding, the TIG welder does not need to adjust the intensity input from the circular segment as the metal is stored from the softening electrode [6]. Garg et al (2019) analyzed that by increasing the welding current on SS304 TIG welding operation, more input heat is generated whereas to sort out the excess heat, extended power is utilized to cool the base metal.…”
Section: Introductionmentioning
confidence: 99%
“…The little serious circular segment given by the sharp anode is great for excellent and accurate welding. Since the cathode will not be consumed during welding, the TIG welder does not need to adjust the intensity input from the circular segment as the metal is stored from the softening electrode [6].…”
Section: Introductionmentioning
confidence: 99%
“…They found that reduced welding voltage significantly affected weld joint hardness and bending strength. Sunny et al, 18 and Sharma and Dwivedi 19 have optimized TIG welding parameters using RSM for super austenitic stainless steel AISI 904L. They developed a second-order quadratic model based on RSM to predict DOP and BW.…”
Section: Introductionmentioning
confidence: 99%